Kerja Sama China-Afrika dalam Konteks Perdagangan dan Investasi: Implikasi bagi Kemitraan Global - Agnes Clara Andika (Terekam Jejak Publisher, 2023)
China along with countries on the African continent have experienced several developments in recent years, especially in terms of trade and investment. This collaboration has broad implications for global partnerships and also drives changes in the dynamics of the global economy. The implication for the global partnership is that China-Africa cooperation in changing the landscape of the global economy through increasing the position and shifting the balance of power of China as the protagonist of the global stage. It can also create new opportunities and challenges for other countries willing to partner with Africa. With a relatively increased capacity, China has succeeded in becoming the largest trading partner for countries in Africa. Various Chinese investment sectors in Africa, namely mining, infrastructure, and the manufacturing industry. This investment also makes several contributions to Africa's economic development such as creating jobs and encouraging the transfer of technology and knowledge. However, in this cooperation there are also challenges and implications for global partnerships, due to an imbalance in this regard where there are several countries in Africa that are at risk of being trapped in heavy debt due to infrastructure projects that have been funded by China. Also due to environmental impacts and exploitation of natural resources caused by Chinese investment coupled with concerns that China is also seen as using its economic power to influence politics and geopolitical dynamics in Africa. In order to reduce risks and maximize benefits, a balanced and mutually beneficial partnership between China and Africa is needed. Then, the impact of this cooperation on human rights, sustainable development, and environmental protection needs to be considered by global partnerships.